Chapter 11 "Let's forget that Slovakia is small" GLOBSEC, status-seeking, and agency in informal elite networks - Graef, Alexander (Taylor & Francis, 2024)
This chapter explores the role transnational networks and informal ties play for small-state-status seeking in Central and Eastern Europe. Using the example of Slovakia, I argue that since their accession to Western institutions, these states have continuously sought to carve out a place for themselves on the mental map of European and North American policymakers. Major security-policy conferences have become central nodal points for this kind of activity. They allow the foreign-policy establishment of small states to manage and shape existing status hierarchies by forging personal contacts with decision-makers from more powerful states. I illustrate this phenomenon empirically with reference to the Bratislava Global Security Forum (GLOBSEC), which began in 2005 as a student-led initiative and has since become the main outreach platform of Slovak foreign policymaking.